Efficient Market Hypothesis: An Exploratory Study of FTSE-100 Stock Market - Ullah, Naqeeb; Asghar, Umair (2023)
The weak form of the efficient market hypothesis posits that stock prices reflect all publicly available information in the market but not undisclosed or private information. To empirically validate the weak form of an efficient market hypothesis, ten years of data from 2012 to 2020 was collected for the (FTSE) Financial Times Stock Exchange Group -100 index. Ordinary least square (OLS) regression was used through SPSS software for statistical tests. The regression tests' findings reveal that the beta coefficient's value is greater than or less than 0 for the lag value of t-1, t-2, t-3, t-4, t-5, t-6, t-7, t-8, t-9, and t-10. Since the value of beta coefficients for all lagged returns of t-1 to t-10 periods is not equal to 0, the efficient market hypothesis is rejected. Thus, this invalidates the efficient market hypothesis. Hence, it can be determined that investors can beat the market by analyzing and evaluating past securities or market index trends. Since past trends predict the future, it can be assumed that stocks or indices will perform similarly.